Learning Engineering through the Flipped Classroom Approach- Students' Perspectives - Turnbull, Wendy Fox; Docherty, Paul; Zaka, Pinelopi (Design and Technology Education: An International Journal, 2018)
A flipped classroom approach consists of two distinct parts: direct on-line instruction in the students’ own time and at their own pace, and interactive group learning and problemsolving activities in scheduled classes. This approach has the potential to suit theoretical and practice-based courses such as technology education. This article outlines a study on students’ views of using the flipped classroom approach to learning from the perspective of first and second year engineering students undertaking a module of learning in Dynamics. Engineering, like many technology related courses is both theoretical and practical in nature. The study investigates students’ views of the use of the flipped classroom approach using focus-group and individual interviews after they had experienced it. The flipped classroom approach facilitated students’ exposure to theoretical ideas in their own time through online lectures, thus maximising time for problem solving activity with their face-to-face lecturer support. This research suggests several key factors within two broad categories that students felt influenced their learning. These categories were identified as Perspectives of Lecturer Behaviour and Perspectives on Student Behaviour. The article concludes with a number of recommendations aimed at improving the teaching and learning experiences for students in the flipped classroom and makes links to the potential applications for other design and technology education disciplines